Study On The Biology And Heavy Metal Toxicity On Chironomus Kiiensis Tokunanga And Chironomus Javanus Kieffer (Diptera: Chironomidae) - Ebau, Warrin (2010)

(untitled)
Chironomus kiiensis Tokunanga and Chironomus javanus Kieffer were found to be suitable for use as test organism in both aquatic and sediment toxicity tests. Both species have a relatively short life cycle (C. kiiensis = 20.86 days and C. javanus = 15.14 days) and easy to culture under laboratory conditions using the same method and food. Both species were found to have four instar stages each with C. javanus having longer body and bigger in size. It is difficult to differentiate these two species at larval stages by naked eyes as they look similar. The apparent characteristic that differentiates C. javanus with C. kiiensis is the unusual teeth number (7 teeth) in the premandible. However, these two species were easy to differentiate at adult stage where C. kiiensis is yellowish brown in colour while C. javanus is greenish in colour.